Resolution of conflict between internet domain names and trade marks - Zinatul Ashiqin Zainol (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2008)
The conflict between internet domain names and trade marks, which typically arises over the rights to register and use domain names incorporating word trade marks may be classified into three scenarios of conflict; (i) cybersquatting or abusive registrations of domain names, (ii) legitimate interest cases and (iii) reverse domain name hijacking. Currently, the conflicts are resolved either through the application of the traditional legal models, i.e. litigation, or though its alternative, which is more popularly known as mandatory administrative proceedings. While it seems logical that trade mark rules should be applicable, the present trend involves selective application of trade mark rules. A comparative assessment of various primary and secondary resources in Malaysia, United Kingdom and the United States including Trade Mark legislation, reported court cases and review of Uniform Dispute Resolution Policy (UDRP) and selected national Dispute Resolution Policy (DRP) cases in the ASEAN region reveals that trade mark principles are applied in unfamiliar and unconventional ways to assimilate domain names into the legal landscape. On the premise that there are insufficient correlations between domain names and trade marks in terms of the inherent characteristics and governance, such application has led to unsatisfactory results.